2009
DOI: 10.1007/s10867-009-9135-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical exploration of intrinsic localized modes in an atomic lattice

Abstract: This review focuses attention on the experimental studies of intrinsic localized modes (ILMs) produced in driven atomic lattices. Production methods involve the application of modulational instability under carefully controlled conditions. One experimental approach is to drive the atomic lattice far from equilibrium to produce ILMs, the second is to apply a driver of only modest strength but nearby in frequency to a plane wave mode so that a slow transformation from large amplitude standing waves to ILMs takes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Recently, it has been shown that band-edge normal modes (NMs) can be continued to nonlinear localized vibrations of high energy termed Discrete Breathers (DBs) [15], also known as intrinsic localized modes [17]. DBs are time-periodic, spatially localized solutions emerging generically in discrete networks of nonlinear oscillators [18,19], that have been also observed experimentally in many systems [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that band-edge normal modes (NMs) can be continued to nonlinear localized vibrations of high energy termed Discrete Breathers (DBs) [15], also known as intrinsic localized modes [17]. DBs are time-periodic, spatially localized solutions emerging generically in discrete networks of nonlinear oscillators [18,19], that have been also observed experimentally in many systems [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…(48) and (49), and are continuous, as proved in Appendix F. Moreover, ∂T p (∆φ,λ) ∂λ = β⟨|Z(θ ) + λ| β−1 ⟩ > 0 for any ∆φ from Eq. (51f).…”
Section: Numerical Verification Of Optimal Forcing Waveformsmentioning
confidence: 73%
“…(2). This idea seems rather reasonable, since stable ILMs (elliptic breathers) in finitedimensional Hamiltonian systems are generically characterized as periodic solutions in the center of KAM tori [47], and the dynamics around such periodic solutions would be reduced to the phase controlling discrete breathers, which gives a hint for understanding emerging interesting experimental results such as [48].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…23,[25][26][27] The coefficients for the individual beam can be derived from the nonlinear Euler-Bernoulli beam theory. If u is measured as a fraction of cross-section w x , for example, then b 1 =a 1 $ C 1 w 2 x =L 2 , with the non-dimensionalized prefactor C 1 depending on the normalization of w x chosen, typically being of order 1.…”
Section: Setup Of the Modeling Problemmentioning
confidence: 99%
“…Since then, ILMs have then been found in a wide variety of structures and there has been substantial interest in the theoretical analysis and practical applications of ILMs. [17][18][19][20][21][22][23][24][25][26][27][28][29] In general, most of these works have concentrated on the analysis of the oscillations being described by one variable. In particular case of ILM in cantilever arrays, the one-dimensionality of vibrations was enforced by designing the experiments with the cantilever thickness in the direction of vibration to be much smaller than in the other direction.…”
mentioning
confidence: 99%